Recent Advances in Herbal-Nano Formulation: A Systematic Review - Srinivasan, N. (Asian Journal of Biological and Life Sciences)
Plants have been used in the maintenance and protection of human health since ancient days and these medicinal plants play a dynamic role in preventing diseases. Natural compounds present in medicinal herbs were used to treat a bacterial infection, digestive disorders, respiratory illness, cardiac disorders, cancer, disorders in brain etc. Despite their outstanding therapeutic applications, the phytochemical components have limited solubility in water and thereby affecting bioavailability. In order to make effective use of this property and overcome limitations, novel strategies have been implemented in using medicinal herbs in health care. Nanotechnology has led to numerous scientific discoveries and invention of nano-medicine is tremendous. Nano-drug delivery is an attractive approach in the treatment of life-threatening diseases like cancer and neurological disorders as these nanoparticles could be linked with drugs to actively cross the blood-brain barrier. This review focusses on herbo-nano formulations and methods of delivering phytochemical drug to targeted cells. Nanoformulations have been implemented in research on delivering active herbal components, improving bioavailability and decrease toxic effects of diseases.
Keywords: Herbal drugs; Nanoformulation; Phytochemicals; Secondary metabolites